If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-63=7(x-9)
We simplify the equation to the form, which is simple to understand
-63=7(x-9)
Reorder the terms in parentheses
-63=+(+7x-63)
Remove unnecessary parentheses
-63=+7x-63
We move all terms containing x to the left and all other terms to the right.
-7x=-63+63
We simplify left and right side of the equation.
-7x=0
We divide both sides of the equation by -07 to get x.
x=-0
| 93+3x+18= | | -71-9m=82 | | 4x-4-24=0 | | (x-5y)(5x+y)=0 | | 4e-16+5e=29 | | 8x+6+7x+14= | | 6.3+0.5h=16.3 | | 1.6n+3.8n=54 | | 7.1x-2.8=24.18 | | 56=-8x | | -5y=-12 | | m+4=-3m | | (3x^2-5x-5)+(9x^2+2x+1)= | | 105x+112= | | X^2+0.02x-0.07=0 | | 6.3+0.5=16.3 | | 6(2-r)=15 | | 130+11x-2= | | .6p-.8=.6666p | | x+(-10)=45 | | 9m+4m+6=32 | | 27=5c-48 | | 110+19x-4= | | y+5=55 | | y=4+5x+x^2 | | 14+a=3a+2 | | 2-q=2+q+18 | | X-8.6=-5.1 | | 10+19x-4= | | (x+4)(y-6)=0 | | 12x+-4+10x+10= | | -15-c=4c |